2007
DOI: 10.18474/0749-8004-42.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Fly Traps for the Capture of Horse Flies (Diptera: Tabanidae)

Abstract: A 2-yr study was conducted to examine differences between two commercially available horse fly traps, the Epps® Biting Fly Trap (Farnum Co., Phoenix, AZ) and the Horse Pal® (Newman Enterprises, Omro, WI), placed on three horse farms located in central North Carolina. Traps captured over 8,422 tabanids, representing 4 genera and 19 species. Tabanus quinquevittatus Wiedemann was the most abundant fly collected (2345), followed by the T. lineola F. species complex (2087), T. fulvulus Weidemann (1397) and T. petio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…When comparing the Horse Pal trap with and without bait, it was found that the number of tabanids caught was different, but not significantly different, suggesting that this type of trap is as effective in catching tabanids as the Nzi trap, and it would probably have been more or less effective if it had been tested in the vicinity of horses just like in North America (Watson et al, 2007). There were caught several tabanids in the Horse Pal trap with bait, as the tabanids were attracted by their dependence on the amount of odor released even from greater distances (Lehane, 2005).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…When comparing the Horse Pal trap with and without bait, it was found that the number of tabanids caught was different, but not significantly different, suggesting that this type of trap is as effective in catching tabanids as the Nzi trap, and it would probably have been more or less effective if it had been tested in the vicinity of horses just like in North America (Watson et al, 2007). There were caught several tabanids in the Horse Pal trap with bait, as the tabanids were attracted by their dependence on the amount of odor released even from greater distances (Lehane, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…In the manufacturer's specifications, it was said, among other things, that this trap does not attract other types of flies, including stable flies. The effectiveness of Horse Pal trap in the catching of tabanids was demonstrating by a two summer seasons study made in North Carolina by Watson et al, (2007).…”
Section: Trapsmentioning
confidence: 99%
See 1 more Smart Citation
“…These explain why only female tabanids are attracted to the shiny black spherical visual target of canopy traps, and which polarization characteristics attract them in different behavioural contexts. The Epps horsefly trap is composed of shiny black vertical panels with elongated trays filled with water containing soap to reduce surface tension (Watson et al ., 2007). The efficacy of this trap should also be related to the polarization characteristics of reflected light.…”
Section: Discussionmentioning
confidence: 99%
“…Three trap types were included in our Florida studies. The Horse Pal® (HP) (Newman Enterprises, Omro, WI) described by Watson et al (2007) as a modified Manning trap, is a box-style canopy trap. The HP trap consists of a four-sided pyramid with a square 61-cm long skirted base, a black ball (circumference = 127 cm), and four legs ( Figure 1a).…”
Section: Trapsmentioning
confidence: 99%